Revealing interdyad differences in naturally occurring staff reactions to challenging behaviour of clients with severe or profound intellectual disabilities by means of Clusterwise Hierarchical Classes Analysis (HICLAS). (19th August 2013) - Wilderjans, T. F.; Lambrechts, G.; Maes, B.; Ceulemans, E.
Abstract Background Investigating interdyad (i.e. couples of a client and their usual caregiver) differences in naturally occurring patterns of staff reactions to challenging behaviour (e.g. self‐injurious, stereotyped and aggressive/destructive behaviour) of clients with severe or profound intellectual disabilities is important to optimise client–staff interactions. Most studies, however, fail to combine a naturalistic setup with a person‐level analysis, in that they do not involve a careful inspection of the interdyad differences and similarities. Method In this study, the recently proposed Clusterwise Hierarchical Classes Analysis (HICLAS) method is adopted and applied to data of in which video fragments (recorded in a naturalistic setting) of a client showing challenging behaviour and the staff reacting to it were analysed. In a Clusterwise HICLAS analysis, the staff–client dyads are grouped into a number of clusters and the prototypical behaviour–reaction patterns that are specific for each cluster (i.e. interdyad differences and similarities) are revealed. Results Clusterwise HICLAS discloses clear interdyad differences (and similarities) in the prototypical patterns of clients' challenging behaviour and the associated staff reactions, complementing and qualifying the results of earlier studies in which only general patterns were disclosed. Conclusions The usefulness and clinical relevance of Clusterwise HICLAS is demonstrated. In particular, Clusterwise HICLAS may capture idiosyncratic aspects of staff–client interactions, which may stimulate direct support workers to adopt person‐centred support practices that take the specific abilities of the client into account.